Fungus-feeding phlaeothripine Thysanoptera in the genus Holothrips from Australia and New Caledonia, with a structurally similar new genus, Holoengythrips - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2014)
Ten species of Holothrips, including seven new species, are recognized from Australia, with one further new species from New Caledonia. A new genus, Holoengythrips, is described from Australia, with nine new species that look similar to Holothrips species in having elongate maxillary stylets that are close together medially for the full length of the head. In contrast to species of Holothrips, the species of Holoengythrips are strongly sexually dimorphic, with antennal segment VIII separated from VII and the maxillary stylets more slender, and the males have a pore plate on the eighth sternite. Holoengythrips is therefore considered to be more closely related to Hoplandrothrips.